Diet-Stimulated Marrow Adiposity Fails to Worsen Early, Age-Related Bone Loss - Cody McGrath; Sarah E. Little-Letsinger; Gabriel M. Pagnotti; Buer Sen; Zhihui Xie; Gunes Uzer; Guniz B. Uzer; Xiaopeng Zong; Martin A. Styner; Janet Rubin; Maya Styner (Obesity Facts, 2024)
Introduction: Longitudinal effect of diet-induced obesity on bone is uncertain. Prior work showed both no effect and a decrement in bone density or quality when obesity begins prior to skeletal maturity. We aimed to quantify long-term effects of obesity on bone and bone marrow adipose tissue (BMAT) in adulthood. Methods: Skeletally mature, female C57BL/6 mice (n = 70) aged 12 weeks were randomly allocated to low-fat diet (LFD; 10% kcal fat; n = 30) or high-fat diet (HFD; 60% kcal fat; n = 30), with analyses at 12, 15, 18, and 24 weeks (n = 10/group). Tibial microarchitecture was analyzed by µCT, and volumetric BMAT was quantified via 9.4T MRI/advanced image analysis. Histomorphometry of adipocytes and osteoclasts, and qPCR were performed. Results: Body weight and visceral white adipose tissue accumulated in response to HFD started in adulthood. Trabecular bone parameters declined with advancing experimental age. BV/TV declined 22% in LFD (p = 0.0001) and 17% in HFD (p = 0.0022) by 24 weeks. HFD failed to appreciably alter BV/TV and had negligible impact on other microarchitecture parameters. Both dietary intervention and age accounted for variance in BMAT, with regional differences: distal femoral BMAT was more responsive to diet, while proximal femoral BMAT was more attenuated by age. BMAT increased 60% in the distal metaphysis in HFD at 18 and 24 weeks (p = 0.0011). BMAT in the proximal femoral diaphysis, unchanged by diet, decreased 45% due to age (p = 0.0002). Marrow adipocyte size via histomorphometry supported MRI quantification. Osteoclast number did not differ between groups. Tibial qPCR showed attenuation of some adipose, metabolism, and bone genes. A regulator of fatty acid β-oxidation, cytochrome C (CYCS), was 500% more abundant in HFD bone (p < 0.0001; diet effect). CYCS also increased due to age, but to a lesser extent. HFD mildly increased OCN, TRAP, and SOST. Conclusions: Long-term high fat feeding after skeletal maturity, despite upregulation of visceral adiposity, body weight, and BMAT, failed to attenuate bone microarchitecture. In adulthood, we found aging to be a more potent regulator of microarchitecture than diet-induced obesity.